Didactic teaching strategies based on different learning styles for math in kindergarten Sheldon independent school district - Rangel, Rafael Pantoja; Barajas, María Teresa del Niño Jesús Delgado (Revista AMIUTEM, 2023)
This project presents a study on the effect caused by the implementation of math teaching strategies based on the Felder-Silverman model of different learning styles in the bilingual kindergarten students from the public school, Stephanie Cravens Early Childhood Academy. This school belongs to Sheldon Independent School District located in Houston Texas, USA. Because of the students’ age, the study was focused in the content of the instructional plan that it would have activities, which would reach all different learning styles without worrying about the particular learning style each child may have. It uses an experimental design with a post-test and a control group with which to compare the group that received the experimental treatment, both of random selection. The t - student was used to determine that significant difference existed between the means of the two samples, with that it was determined that the progress of the experimental group surpassed that exhibited by the students in regular classes. In the qualitative part, the students’ confidence was noticed by the proposal, trend supported by the answers on the survey.